Overview of Age and Parity with the Incidence of Placental Retention in Pregnant Women at Dumai City Hospital, Dumai District, Dumai City in 2023 - Lestari, Anggi Suci (Benih : Journal of Midwifery, 2024)
lacental retention is the cause of most cases of postpartum hemorrhage while postpartum hemorrhage is the cause of the most maternal deaths in Indonesia. This study aims to determine the age and parity with the incidence of placental retention in pregnant women at Dumai City Hospital, Dumai District, Dumai City in 2023. This research is a descriptive research with a survey method. The population is 35 people. The sampling technique uses the total sampling technique, where all populations are sampled as many as 35 postpartum mothers. Data collection uses primary data using questionnaires. The data was processed, presented by Frequency and Cross Tabulation and then analyzed by Chi-square Test. The results of the study showed that the majority of mothers were 20-35 years old as many as 21 people (60.0%) and the majority parity of Scundipara was 15 people (42.9%). The incidence of placental retention in pregnant women at Dumai City Hospital, Dumai District, Dumai City in 2023 is as many as 14 people (40.0%). The results of data analysis for age with the chi square test obtained p value = 0.007 (p<0.05) which showed that there was a relationship between age and the incidence of placental retention in pregnant women. The results of data analysis for parity with the chi square test obtained p value = 0.001 (p<0.05) which means that there is a relationship between parity and the incidence of placental retention in pregnant women. The conclusion of this study is that there is a relationship between age and parity with the incidence of placental retention in pregnant women at Dumai City Hospital, Dumai District, Dumai City in 2023. :P health workers, especially midwives, should be able to handle placental retention quickly and appropriately so that the incidence of primary postpartum hemorrhage and maternal mortality can be minimized.